Facile preparation of etched halloysite@polyaniline nanorods and their enhanced electrochemical capacitance performance. (20th October 2019) - Zhao, Yue; Li, Yan'ge; Quan, Xiangjun; Li, Cuiping
Abstract: One-dimensional etched halloysite@polyaniline (eHA@PANI) nanorods with great specific capacitance are prepared by in combination of acid selective etching and aniline in-situ polymerization. By conveniently conditioning dopant acids/synthesis temperature and etching time in the fabrication, the doping degree/redox states (Q/B) of PANI growing on eHA nanorods and the specific surface area of eHA can be respectively controllable. eHA@PANI is characterized by TEM, FT-IR, UV-vis, XPS, XRD, EIS and organic elemental analysis. Meanwhile, the electrochemical performance of eHA@PANI is assessed by cyclic voltammetry (CV) and galvanostatic charge/discharge (GCD). It indicates that eHA@PANI electrodes prepared with eHA/18 h as support, HCl as doping acid and 0 °C reaction temperature (eHA/18 h-PANI-HCl-0 o C) achieve the highest specific capacitance (711.1 F g −1 ) at the current density of 1 A g −1 . The specific capacitance matches well with the doping degree of PANI in eHA@PANI and electrical conductivity of eHA@PANI. Furthermore, it also shows good cycling stability (specific capacitance retention ratio can achieve 77.6% after 300 charge-discharge cycles), demonstrating it is a potential electrode material for high-performing supercapacitors. Graphical abstract: Enhanced electrochemical capacitance performance of etched halloysite@polyaniline nanorods was prepared by acid selective etching and aniline in-situ polymerization at 0 °C.Image 1